Preparation method of perovskite film blue light gain medium

Through the preparation of perovskite films, a symmetric waveguide structure is formed, which solves the problem of high growth cost of the gain medium of existing semiconductor lasers and mismatch of lattice, achieving blue light laser emission and stability with low threshold and high light gain, suitable for high humidity environment.

CN119315384AActive Publication Date: 2025-01-14ZHEJIANG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411247206.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-14
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The gain medium growth process of existing semiconductor lasers depends on ultra-high vacuum conditions, high equipment and energy consumption costs, and the mismatch with the crystal lattice of silicon-based substrates limits the development of semiconductor lasers, lacking blue light excitation with low threshold and high light gain. ejaculation medium.

Method used

By using the preparation method of perovskite film blue light gain medium, perovskite precursor and polyacrylonitrile dissolved in ultra-dry dimethyl sulfoxide, a perovskite film was formed on the glass substrate by spin coating method to form a perovskite film. The symmetric waveguide structure of "polyacrylonitrile-perovskite-polyacrylonitrile" enhances the restriction effect of photons and improves spectral stability.

Benefits of technology

The blue light laser with low threshold and high light gain is achieved, with good stability in high humidity environments, reducing equipment and energy consumption costs, and easy integration with other optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315384A_ABST
    Figure CN119315384A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a perovskite film blue light gain medium, and the method comprises the following steps: S1, raw material blending: dissolving a perovskite precursor and polyacrylonitrile (PAN) in ultra-dry dimethyl sulfoxide to obtain a mixed solution; wherein the mass ratio of the polyacrylonitrile (PAN) to the perovskite precursor is (0.3-0.4): 1; and S2, spin-coating film formation: taking the mixed solution on a glass substrate, and performing spin-coating film formation in an inert gas environment by using a spin-coating method to obtain the perovskite thin film blue light gain medium. The perovskite thin film prepared by the method can realize blue light lasing with low threshold and high optical gain, and has good stability in a high-humidity environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser gain medium materials, and in particular relates to a method for preparing a perovskite thin film blue light gain medium. Background Art

[0002] Semiconductor lasers have the advantages of ultra-small size, high efficiency, low power consumption, long life and high-speed modulation, and are widely used in optical communications, optical information processing, laser display and intelligent driving. Among them, semiconductor gain medium, as the core component of semiconductor lasers, directly determines the performance of semiconductor lasers.

[0003] The gain media of commercial semiconductor lasers are generally III-V compound semiconductors such as gallium arsenide (GaAs), indium phosphide (InP), and gallium nitride (GaN). Their growth process often relies on epitaxial technology under ultra-high vacuum conditions, which has harsh growth conditions and high equipment and energy costs. At the same time, epitaxial growth depends on lattice matching. The lattice mismatch between compound semiconductors and commonly used silicon-based substrates has also greatly restricted the development of semiconductor lasers. Correspondingly, lead halide perovskite films have the advantages of high optical gain, adjustable bandgap, non-epitaxial growth, and easy integration with other optoelectronic devices. They are strong competitors for the next generation of low-cost, high-performance full-color laser gain media.

[0004] Therefore, it is necessary to propose a perovskite thin film blue light gain medium that can achieve low threshold, high optical gain blue light lasing and good stability for the lead halide perovskite technology route. This perovskite thin film blue light gain medium is specially designed for gain in the blue light region, has significant optical gain characteristics in the blue light band, and can achieve low threshold blue light lasing or amplification, which is of great significance for improving the performance and stability of blue light lasers. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a perovskite film blue light gain medium. The perovskite film prepared by the method can achieve low threshold, high optical gain blue light lasing and has good stability in a high humidity environment.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a perovskite thin film blue light gain medium comprises the following steps:

[0008] S1. Raw material blending: dissolving a perovskite precursor and polyacrylonitrile (PAN) in ultra-dry dimethyl sulfoxide to obtain a mixed solution; wherein the mass ratio of the polyacrylonitrile (PAN) to the perovskite precursor is (0.3-0.4):1;

[0009] S2. Spin coating: The mixed solution is placed on a glass substrate and is spin coated in an inert gas environment to obtain a perovskite thin film blue light gain medium.

[0010] Furthermore, the perovskite precursor consists of CsCl, PbCl2 and PbBr2.

[0011] Further, the concentration ratio of CsCl, PbCl2 and PbBr2 is 4:1:3. For example, in the embodiment of the present invention, the concentrations of CsCl, PbCl2 and PbBr2 are 0.12M, 0.03M and 0.09M respectively. The above concentrations are only for enumeration and do not constitute a specific limitation on the concentration of the perovskite precursor of the present invention. All within the protection concept of the present invention belong to the protection scope of the present invention.

[0012] Furthermore, the glass substrate is a pre-treated glass substrate;

[0013] The pretreatment method is: the glass substrate is ultrasonically cleaned in acetone, deionized water and anhydrous ethanol in sequence for 30 minutes, blown dry with a nitrogen gun, and then placed in an oxygen plasma machine for surface treatment for 10 minutes.

[0014] Furthermore, the spin coating process in step S2 is performed in a glove box, and the glove box is filled with nitrogen.

[0015] Furthermore, the spin coating film forming condition parameters of step S2 are: rotation speed 2000 rpm, spin coating time 120 s; after the spin coating is completed, it is placed on a heating plate at 100° C. for annealing for 10 min.

[0016] Furthermore, the perovskite thin film blue light gain medium has a symmetrical waveguide structure of "polyacrylonitrile-perovskite-polyacrylonitrile".

[0017] Furthermore, the symmetrical waveguide structure is formed in-situ during the process of spin coating the perovskite film.

[0018] Furthermore, the refractive index of the polyacrylonitrile is smaller than that of perovskite to enhance the confinement effect of photons; the perovskite film blue light gain medium can be at 21.9 μJ / cm 2 Blue light amplified spontaneous emission is achieved under low threshold excitation conditions.

[0019] Beneficial effects of the present invention:

[0020] (1) Polyacrylonitrile is added as an additive to the perovskite precursor solution, and high-quality perovskite film can be prepared by a one-step spin coating method. Among them, polyacrylonitrile is concentrated on the buried interface and upper surface of the film, forming a natural "polyacrylonitrile-perovskite-polyacrylonitrile" symmetrical waveguide structure in situ, enhancing the film's confinement effect on photons. At the same time, the in-situ coordination coating of the polyacrylonitrile matrix on the perovskite grains can effectively passivate the defects in the perovskite while increasing the ion migration barrier in the perovskite and enhancing the spectral stability. In addition, polyacrylonitrile can significantly improve the surface morphology and increase the film thickness to reduce scattering loss and increase modal constraints. Finally, the perovskite film can achieve low-threshold, high-light gain blue light lasing, and has good stability in a high humidity environment.

[0021] (2) By introducing 30%-40% by mass of polyacrylonitrile into the perovskite precursor solution, a natural "polyacrylonitrile-perovskite-polyacrylonitrile" sandwich structure is formed in situ during the one-step spin coating of the perovskite film. Since the refractive index of polyacrylonitrile is smaller than that of perovskite, a symmetric waveguide structure can be formed, which enhances the confinement effect of photons and improves the lasing properties of the perovskite film. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A cross-sectional high-angle annular dark-field image and element distribution diagram of the perovskite thin film blue light gain medium prepared in Example 1;

[0023] Figure 2 Schematic comparison diagram of the symmetrical waveguide structure of the perovskite thin film blue light gain medium sample prepared in Example 1 (left side) and Comparative Example 1 (right side);

[0024] Figure 3 The normalized fluorescence spectra of the perovskite film (a) of Comparative Example 1 and the perovskite film (b) of Example 1 under continuous irradiation of continuous wave laser;

[0025] Figure 4 The blue light lasing characteristics of the perovskite film blue light gain medium of Example 1 are shown in FIG. 1 . The gain medium can emit blue light at 21.9 μJ / cm 2 Blue light amplified spontaneous emission can be achieved under low threshold excitation conditions;

[0026] Figure 5 This is an analysis of the effect of different PAN addition amounts on the amplified spontaneous emission threshold of perovskite films. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described here are only used to explain the present invention and are not used to limit the present invention.

[0028] Embodiment 1:

[0029] Weigh CsCl, PbCl2, PbBr2 and polyacrylonitrile (PAN) and dissolve them in ultra-dry dimethyl sulfoxide. According to 1mL of dimethyl sulfoxide, the mass of CsCl, PbCl2 and PbBr2 are 20.2mg, 8.3mg and 30.3mg respectively, so that the concentrations of CsCl, PbCl2 and PbBr2 in the precursor solution are 0.12M, 0.03M and 0.09M respectively. Polyacrylonitrile (PAN) is added to the precursor solution at a mass fraction of 35% and stirred to ensure full dissolution. The glass substrate is ultrasonically cleaned in acetone, deionized water and anhydrous ethanol for 30min in turn, dried with a nitrogen gun and placed in an oxygen plasma machine for surface treatment for 10min. After completion, it is transferred to a glove box for standby use. Take an appropriate amount of precursor solution in the center of the glass substrate (for a 15*15mm glass substrate, the typical value is 50 microliters), and spin-coat it into a film using a one-step spin coating method, with a rotation speed of 2000 rpm and a spin coating time of 120s. After the spin coating, the film was placed on a hot plate at 100°C for annealing for 10 minutes. The entire film preparation process was carried out in a glove box filled with nitrogen to obtain a perovskite film blue light gain medium.

[0030] Experimental analysis: Figure 1 As shown, the cross-sectional high-angle annular dark field image and element distribution diagram of the perovskite film blue light gain medium sample prepared in Example 1; due to the presence of heavy metal lead in the perovskite, the perovskite shows obvious contrast compared to the polymer matrix. The lead element is mainly distributed in the central area of ​​the cross-sectional direction, and the carbon element is concentrated on the upper and lower surfaces. It shows that in the vertical direction of the film, PAN shows obvious segregation phenomenon, which is concentrated on the buried interface and upper surface of the perovskite layer, and the perovskite is coated therein.

[0031] like Figure 2 , which is a schematic diagram of the symmetrical waveguide structure of "polyacrylonitrile-perovskite-polyacrylonitrile" of the present invention. In Example 1, since the upper and lower surfaces of the perovskite are coated with polyacrylonitrile, and the refractive index of polyacrylonitrile is lower than that of the perovskite, a natural symmetrical waveguide structure is formed in the film, and the photons are confined in the perovskite. Correspondingly, in Comparative Example 1, since there is no coordination coating of polyacrylonitrile, there is no symmetrical waveguide structure in the film, and the photon confinement effect is significantly reduced.

[0032] like Figure 3 As shown, the perovskite film of Comparative Example 1 is 2 The spectrum shift occurs in only about 20 seconds under low-density excitation, while the perovskite film of Example 1 2The blue light emission can be maintained stably even after 2 hours of continuous irradiation under high excitation density. This indicates that the spectral stability of the perovskite film is significantly improved after adding PAN.

[0033] like Figure 4 As shown in the figure, the blue light lasing characteristics of the perovskite film blue light gain medium of Example 1, the gain medium can be 21.9μJ / cm 2 Blue light amplified spontaneous emission is achieved under low threshold excitation conditions.

[0034] Embodiment 2:

[0035] Weigh CsCl, PbCl2, PbBr2 and polyacrylonitrile (PAN) and dissolve them in ultra-dry dimethyl sulfoxide. The concentrations of CsCl, PbCl2 and PbBr2 in the precursor solution are 0.12M, 0.03M and 0.09M respectively. Add 30% of polyacrylonitrile (PAN) into the precursor solution and stir to ensure full dissolution. The thin film spin coating method is the same as that in Example 1.

[0036] Embodiment 3:

[0037] Weigh CsCl, PbCl2, PbBr2 and polyacrylonitrile (PAN) and dissolve them in ultra-dry dimethyl sulfoxide. The concentrations of CsCl, PbCl2 and PbBr2 in the precursor solution are 0.12M, 0.03M and 0.09M respectively. Add 40% of polyacrylonitrile (PAN) into the precursor solution and stir to ensure full dissolution. The thin film spin coating method is the same as that in Example 1.

[0038] Comparative Example 1:

[0039] Weigh CsCl, PbCl2, and PbBr2 and dissolve them in ultra-dry dimethyl sulfoxide. The concentrations of CsCl, PbCl2, and PbBr2 in the precursor solution are 0.12 M, 0.03 M, and 0.09 M, respectively. Stir to ensure full dissolution. The spin coating method is the same as in Example 1.

[0040] Comparative Example 2:

[0041] Weigh CsCl, PbCl2, and PbBr2 and dissolve them in ultra-dry dimethyl sulfoxide. The concentrations of CsCl, PbCl2, and PbBr2 in the precursor solution are 0.12M, 0.03M, and 0.09M, respectively. Stir to ensure full dissolution. Add 10% by mass of polyacrylonitrile (PAN) to the precursor solution and stir to ensure full dissolution. The thin film spin coating method is the same as in Example 1.

[0042] like Figure 5As shown, it is an analysis diagram of the effect of different PAN addition amounts on the amplified spontaneous emission threshold of the perovskite film. The films in comparative examples 1 and 2 cannot generate amplified spontaneous emission. However, embodiments 1, 2 and 3 with natural symmetrical waveguide structures can all achieve low-threshold amplified spontaneous emission.

[0043] The present invention illustrates the detailed preparation method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed preparation method, that is, it does not mean that the present invention must rely on the above-mentioned products and detailed preparation methods to be implemented. It should be clear to those skilled in the art that any improvement of the present invention, the combination or equivalent replacement of the raw materials of the product of the present invention, all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a perovskite thin film blue light gain medium, characterized in that: The steps include: S1. Raw material blending: dissolving a perovskite precursor and polyacrylonitrile (PAN) in ultra-dry dimethyl sulfoxide to obtain a mixed solution; wherein the mass ratio of the polyacrylonitrile (PAN) to the perovskite precursor is (0.3-0.4):1; S2. Spin coating: The mixed solution is placed on a glass substrate and is spin coated in an inert gas environment to obtain a perovskite thin film blue light gain medium.

2. The method for preparing a perovskite thin film blue light gain medium according to claim 1, characterized in that: The perovskite precursor consists of CsCl, PbCl2 and PbBr2.

3. The method for preparing a perovskite thin film blue light gain medium according to claim 2, characterized in that: The concentration ratio of CsCl, PbCl2 and PbBr2 is 4:1:

3.

4. The method for preparing a perovskite thin film blue light gain medium according to claim 1, characterized in that: The glass substrate is a pre-treated glass substrate; The pretreatment method is: the glass substrate is ultrasonically cleaned in acetone, deionized water and anhydrous ethanol in sequence for 30 minutes, blown dry with a nitrogen gun, and then placed in an oxygen plasma machine for surface treatment for 10 minutes.

5. The method for preparing a perovskite thin film blue light gain medium according to claim 4, characterized in that: The spin coating process in step S2 is performed in a glove box filled with nitrogen.

6. The method for preparing a perovskite thin film blue light gain medium according to claim 1, characterized in that: The spin coating film forming condition parameters of step S2 are: rotation speed 2000 rpm, spin coating time 120s; after the spin coating is completed, it is placed on a heating plate at 100° C. for annealing for 10 minutes.

7. The method for preparing a perovskite thin film blue light gain medium according to claim 1, characterized in that: The perovskite film blue light gain medium has a symmetrical waveguide structure of "polyacrylonitrile-perovskite-polyacrylonitrile".

8. The method for preparing a perovskite thin film blue light gain medium according to claim 7, characterized in that: The symmetrical waveguide structure is formed in situ during the spin coating of the perovskite film.

9. The method for preparing a perovskite thin film blue light gain medium according to claim 8, characterized in that: The refractive index of the polyacrylonitrile is lower than that of the perovskite to enhance the confinement effect of photons; The perovskite thin film blue light gain medium can achieve 21.9 μJ / cm 2 Blue light amplified spontaneous emission is achieved under low threshold excitation conditions.

Citation Information

Patent Citations

  • Colloid quantum dot continuous laser and preparation method thereof

    CN108376901A

  • Flexible circular polarization liquid crystal laser based on perovskite quantum dots as well as preparation method and application of flexible circular polarization liquid crystal laser

    CN117117616A

  • Method for preparing pure-phase quasi-two-dimensional perovskite thin film with adjustable layer number by utilizing polymer crystallization

    CN117897021A

  • Perovskite / polymer composite luminescent material, preparation method and use

    US20180298278A1